Kollagenosen Der aktuelle Wissensstand zu Diagnostik, Klinik und Therapie - Schneider, Matthias; Witte, Torsten (De Gruyter, 2020)
Connective tissues diseases are complex illnesses that very often exhibit the differential diagnosis of inflammatory disease. In this book, experts present individual connective tissues diseases, including their epidemiology, pathogenesis, autoantibodies/biomarkers, manifestations, and therapy options. The clinical images are clearly explained, and rheumatologists will find interesting innovations with a view to diagnostics and therapy.